Adaptive position tracking control of electro-hydraulic six-degree-of-freedom driving simulator subject to perturbation. (March 2015) - Zhao, Qiang; Wang, Na; Spencer, Billie F
In this paper, a new Lyapunov-based adaptive control scheme for the position tracking of an electro-hydraulic Stewart–Gough platform type six-degree-of-freedom (DOF) driving simulator is proposed. The kinematics and the dynamics of both the moving platform and the hydraulic actuator are first derived, and the linearized dynamic equation of the moving platform is developed for the controller design. Two control loops are employed, in which the platform controller is in the outer loop and the actuator controllers are in the inner loop. In the platform controller, the compound proportional-differential (PD) feedback and adaptive compensation controller is designed. The PD part is used to create the principal control signal, and the adaptive part is used to compensate for the parameter uncertainty and external disturbance. To suppose that the upper bound of the perturbation is known, a gradient descent method-based adaptive law is developed for parameter estimation. For each actuator controller a servo force control scheme is designed to ensure the actuator to accurately track the desired force output by the platform controller. All the controllers are designed together based on the Lyapunov method to guarantee the stability of the whole system. Numerical simulation on a six-DOF simulator shows that the proposed control scheme has better tracking performance than its non-adaptive counterpart.